2010
DOI: 10.1096/fj.10-169417
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative protein thymosin β‐4 is a novel regulator of purinergic signaling

Abstract: By an unknown mechanism, β-thymosins are extracellular modulators of angiogenesis, inflammation, wound healing, and development. We were interested in identifying β-thymosin interactors and determining their importance in β-thymosins signaling in human vein endothelial cells (HUVECs). We performed pulldown experiments with biotinylated thymosin β-4 (Tβ4) in comparison to neutravidin beads alone and used mass spectrometric analysis to identify differentially interacting proteins. By this method, we identified F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 36 publications
2
58
0
Order By: Relevance
“…4,13,64 A candidate extracellular receptor of high affinity for Tβ4 is the β subunit of cell surface-located ATP synthase, which would allow extracellular Tβ4 to signal via a purinergic receptor to promote endothelial cell migration. 19 Tβ4 induces endothelial progenitor cell migration via the PI3K/Akt/eNOS signal transduction pathway. 51 Internalization of exogenous Tβ4 may be responsible for the antiapoptotic effects of exogenous Tβ4 on human corneal epithelial cells 24 Internalization of the exogenous Tβ4 followed by activation of integrin-linked kinase and Akt seem to be the major mechanisms that promote the survival of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…4,13,64 A candidate extracellular receptor of high affinity for Tβ4 is the β subunit of cell surface-located ATP synthase, which would allow extracellular Tβ4 to signal via a purinergic receptor to promote endothelial cell migration. 19 Tβ4 induces endothelial progenitor cell migration via the PI3K/Akt/eNOS signal transduction pathway. 51 Internalization of exogenous Tβ4 may be responsible for the antiapoptotic effects of exogenous Tβ4 on human corneal epithelial cells 24 Internalization of the exogenous Tβ4 followed by activation of integrin-linked kinase and Akt seem to be the major mechanisms that promote the survival of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been debate regarding its contribution to extracellular ATP synthesis [78], F1F0 synthase appears to be an important positive regulator of endothelial cell migration [79][80][81]. Interestingly, F1F0 synthase is also the major endothelial binding site for angiostatin, a potent inhibitor of angiogenesis and endothelial cell migration [82,83].…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…Recently it was reported that TB4 increases extracellular ATP synthesis and possibly induces purine receptormediated endothelial cell migration [3]. This encouraged us to screen plasma samples for ATP and ADP and for activities of soluble purine-converting enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the Akt pathway decreases cell necrosis and apoptosis as well as inflammation after ischemic insult in the heart [2]. Recently TB4 was linked to increased cell surface ATP production by acting through extracellular ATP synthase and it was speculated that the increase in local ATP production could influence cell behavior through purinergic signaling [3].…”
Section: Introductionmentioning
confidence: 99%